Meningkatkan kemampuan pemecahan masalah matematis siswa: Pengembangan modul pembelajaran berbasis studi etnomatematika pada budidaya tanaman hidroponik - Nisa, Mir Atun; Kumala, Fitria Zana (Mahesa Research Center, 2024)
This study aims to develop an ethnomathematical study-based learning module on hydroponic plant cultivation to improve the mathematical problem-solving ability of class VII junior high school students on social arithmetic material that meets the criteria of validity and effectiveness. This research method is research and development with the ADDIE model (analysis, design, development, implementation, evaluation). Data collection instruments include interviews, validation sheets, questionnaires, and pre-test and post-test questions. The data were analyzed using qualitative and quantitative data analysis techniques. The results showed that ethnomathematics research-based learning modules were considered effective and feasible, with a percentage of 90% results verified by material and ethnomathematics experts, 96% by media experts, 90% teacher assessments, and a pass rate of group examination assessments of 87.3%, and a pass rate of on-site examination evaluations of 88.61%. The modules developed are also claimed to be effective in improving students' mathematical solving skills, with the experimental class having an average N-gain score of 0.78 in the